SEJUMLAH SKANDAL PEMIMPIN POLITIK DI INDONESIA: SIGNIFIKANSI TERHADAP KELUARAN 18: 21 - Putra, Andreas (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2024)
This article examines the scandal of political leaders in Indonesia through a literature analysis and Biblical analysis method, with a specific focus on the significance of Exodus 18:21. The study aims to explore the reasons behind the recurring pattern of scandals involving political leaders in Indonesia and to provide a Biblical perspective on the issue. By analyzing the political landscape from various literatures, the main causes of these scandals will be identified, and then compared and contrasted with the principles outlined in Exodus 18:21. The findings suggest that the ethical framework provided in Exodus 18:21 can serve as a crucial guideline for political leaders in Indonesia, offering insights on effective governance, accountability, and integrity.